Education of Citizenship in Higher Education as A Fortress of Nation Characters in Facing Era Society 5.0 - Yusuf Falaq (Journal of Educational Sciences, 2020)
This article is the result of thinking about the position of citizenship education in higher education as a bastion of the nation's character in facing the era of Society 5.0. The national education system Citizenship Education is an integrative part that is realized in the form of curriculum and learning in all lines and levels of education. Various functions and roles of citizenship education in the context of achieving national education goals are designed, and implemented as a form of manifestation. The nation's character is absolutely necessary in the middle of Era Society 5.0 which demands that society be able to control and balance the ability of artificial intelligence and social intelligence to solve all kinds of national problems. Society 5.0 provides an illustration that everything can be mobilized and linked through data, including as an effort to overcome social problems. In conclusion, students are equipped with skills needed in the era of society 5.0, including: leadership, digital literacy, communication, emotional intelligence, entrepreneurship, global citizenship. Citizenship education has the challenge of presenting critical, constructive and innovative thinking knowledge and skills by not leaving emotional, social and spiritual intelligence firmly entrenched as mandated in the Pancasila and the 1945 Constitution.